Towards clinical development of a Pfs48/45-based transmission blocking malaria vaccine - Michael Theisen; Matthijs M. Jore; Robert Sauerwein (Expert Review of Vaccines, 2017)
Introduction: Malaria is a devastating vector-borne disease caused by the Plasmodium parasite, resulting in almost 0.5 million casualties per year. The parasite has a complex life-cycle that includes asexual replication in human red blood cells, causing symptomatic malaria, and sexual stages which are essential for the transmission to the mosquito vector. A vaccine targeting the sexual stages of the parasite and thus blocking transmission will be instrumental for the eradication of malaria. One of the leading transmission blocking vaccine candidates is the sexual stage antigen Pfs48/45. Areas covered: PubMed was searched to review the progress and future prospects for clinical development of a Pfs48/45-based subunit vaccine. We will focus on biological function, naturally acquired immunity, functional activity of specific antibodies, sequence diversity, production of recombinant protein and preclinical studies. Expert commentary: Pfs48/45 is one of the lead-candidates for a transmission blocking vaccine and should be further explored in clinical trials.